Nitrogen supply and other controls of carbon uptake of understory vegetation in a boreal Picea abies forest - Palmroth, Sari; Bach, Lisbet H.; Lindh, Marie; Kolari, Pasi; Nordin, Annika; Palmqvist, Kristin (Agricultural and Forest Meteorology, 2021)
In boreal forests, carbon (C) uptake by understory may be too large to be ignored and too variable in space to be assumed a constant fraction of the ecosystem gross primary production. To improve estimates of understory production in these ecosystems, we need to better account for its main controls. In this study, we estimated C uptake of field-layer vegetation, dominated by Vaccinium myrtillus, V. vitis-idaea, and Deschampsia flexuosa, in a boreal Picea abies stand in northern Sweden. Nitrogen (N) availability in the stand has been manipulated through annual N additions since 1996 at the rates of 0, 12.5, and 50 kg N ha(-1) yr(-1). To assess the relative importance of N supply, and interannual fluctuations in leaf biomass and weather, in controlling field-layer photosynthetic production, we calculated C uptake over eight growing seasons using a canopy photosynthesis model. Without N additions, tree leaf area index (L) was already high (8.5) and field-layer C uptake was small, 27 g Cm-2 (or similar to 3% of stand C uptake). An increase in tree L with N additions further reduced light availability for the understory, yet the concurrent increase in the relative abundance of the more physiologically active D. flexuosa sustained the contribution of the field-layer to stand photosynthetic production. Based on a literature survey, in which site quality or stand age generated a wide range in L, understory contribution to ecosystem C uptake increases linearly with the fraction of available light reaching the forest floor across high latitude forests. Understory contributes only similar to 5% to ecosystem C uptake where trees intercept similar to 80% of incoming light, increasing to 100% after clearcut tree harvest. While the availability of solar energy, both spatially and temporally, is the primary driver of understory production, our analyses suggest that the predicted increases in drought severity and frequency at high latitudes may affect understory communities more than trees. Future empirical and modeling studies ...